Increasing Knowledge and Attitudes of Genital Care during Menstruation through Audio Visual Aids: Peningkatan Pengetahuan dan Sikap Perawatan Genitalia saat Menstruasi melalui Audio Visual Aids - Feistangelis Tiak; Sri Restu Tempali; Sri Yanti Kusika; Mardiani Mangun; Narmin; Asriwidyayanti (Napande: Jurnal Bidan, 2024)
Background: Adolescent knowledge about genital care during menstruation is currently very low, interviews from 10 students said they had menstruated but 7 students did not understand how to care for genitalia during menstruation, 5 students had experienced vaginal discharge, therefore counseling was conducted using Audio Visual Aids (AVA). Objective: To determine the effect of counseling using AVA on genital care during menstruation on the attitude & knowledge of female students. Methods: Quasi-experiment in the form of pretest-posttest, population of 134 students, sample size of 81 students, instrument in the form of a questionnaire, data processing using SPSS program calculation, data analysis using Wilcoxon test. Results: There is an effect of counseling using AVA on genital care during menstruation on the attitude & knowledge of female students. The results indicate that after being given treatment, most are in a good category, namely knowledge 87.7% & attitude 97.5%. With a p-value analysis of 0.000 (p <0.05). Conclusion: Counseling using AVA can develop the knowledge & attitude of female students about genital care during menstruation. Suggestion: Scheduled counseling using AVA can be done, so that it can be given to respondents and accessed anywhere.